Determinants of willingness to practice medicine in underdeveloped areas: Evidence from a survey on Iranian medical students. Issue 1 (22nd February 2019) - Rezaei, Satar; Hajizadeh, Mohammad; Kazemi Karyani, Ali; Soltani, Shahin; Asadi, Heshmatollah; Bazyar, Mohammad; Mohammadi, Zahra; Kazemzadeh, Neshat; Nouri, Bijan
Abstract : Purpose: Appropriate access to formally-trained health workers for people living in rural and underdeveloped areas is a continuing challenge worldwide. The purpose of this paper is to investigate the willingness of formally-trained health workers to practice in underdeveloped areas and its main determinants among medical students in the western provinces of Iran. Design/methodology/approach: A total of 753 medical students from four provinces in western Iran (Kermanshah, Ilam, Lorestan and Kurdistan) were surveyed cross-sectionally in 2017. A self-administrated questionnaire was used to collect data on sociodemographic characteristics, willingness to practice in underdeveloped areas, intrinsic (e.g. desire to help others and self-interest in medicine) and extrinsic (e.g. the high income of physicians and social prestige) motivations of the study population. Multivariable logistic regression was used to identify the main determinants of willingness to practice in underdeveloped areas among medical students after their graduation. Findings: The results indicated that 58.3 percent of students were willing to practice in underdeveloped areas. While 59 percent of the study population had a strong extrinsic motivation to study medicine, the remaining 41 percent of the study population had a strong intrinsic motivation to study medicine. The logistic regression results indicated that low parental professional and educational status, an experience of living in rural areas and having strong intrinsic motivation were associated with greater willingness to practice in underdeveloped areas. Originality/value: This is the first study to investigate the willingness to practice in underdeveloped areas and its main determinants among medical students in the west of Iran.